Monkeypox transmission risks in Indonesia - Saputra, Hermawan; Salma, Nadilah; Anjari, Sheila Rizkia (Public Health of Indonesia, 2022)
After half a century as a regional disease in Central and West Africa, Monkeypox reemerged in 2022 and spread on a transnational and transcontinental scale. The World Health Organization (WHO) classified it as a Public Health Emergency of International Concern due to its rapid spread caused by the ease of global mobilization, risk deviant behaviors, and potential for virus mutations. Through literature review and other secondary data sources, this study scrutinized the risk of Monkeypox disease in Indonesia. Given the country's various characteristics, such as geographical conditions, demographics, population mobility, and virus characteristics, it is most likely that there were Monkeypox cases in Indonesia, but they might not have been detected. Therefore, early vigilance must be owned by the community and accompanied by policy support and intervention to prevent Monkeypox transmission, particularly in surveillance efforts.